Aspergillus spp. and azole-resistance characterization on mechanic protection gloves from waste sorting industry - Viegas, Carla (2020)
Aspergillus spp. species are filamentous fungi commonly found in different environmental compartments, where they thrive as saprophytes. Some species among the Aspergillus genera can be occasionally harmful to humans. Only a few species are considered as significant opportunistic pathogens in humans. Aspergillus section Fumigati is an opportunistic pathogen of immunocompromised hosts and one of several Aspergillus species that cause a wide range of respiratory disorders. Increased occurrence of opportunistic Aspergillus infections in immunocompromised patients, and the emergence of antifungal resistance, either in the clinical or in the environment had been reported.